Elucidative to activity of Large monastery in Ukraine (XVII– XVIIІ in.) (Pedagogy of Higher and Secondary Education, 2013)
Fazan V. V. Elucidative to activity of Large monastery in Ukraine (XVII– XVIIІ in.)Pre-conditions are considered and described which was instrumental in becoming of elucidative activity Large monasteries in Ukraini. Positive influence of Large monasteries is analysed on formation of society.
Keywords: education; Large monasteries; divinity; spirituality; religious education